El trascendental unum en la ontología aristotélico-tomista - Cresta, Norberto Gerald (Sapientia, 2020)
Thomas Aquinas follows Aristotle in his conception of the fundamental constitutive of the transcendental: not being reducible to supreme genres. In the case of the transcendental unum, despite the demands of intelligibility that tend towards a formal principle of unity, it acquires the same relevance as the first transcendental ens. A conceptual difficulty then arises: on the one hand, the impossibility of being thought as a first formal principle from which deduce the reality of the substance or the remaining transcendental ones, on the other hand, the unum is radically a priori and constitutes an expression of the ens in the fullness of its act of being, since it manifests the transcendent origin of its multiple determinations. This paper analyzes the study of the transcendental unum in the Aristotelian-Thomistic tradition and raises related questions about the formalization of the sciences in view of a concept that, not being substance or formal principle, provides an explanation of being. It is significant within this context the relevance that Thomas Aquinas gives to the human cognitive dimension as part of the expressive dynamism of the transcendental, in such a way that the relationship between man and nature and the world acquires special importance in the face of conceptions of being that, in their absolute transcendence, reduce or deny the intellectual participation. In this sense, we propose options for reflection on the transcendental ones that validate their radical expressiveness of the entity at the same time as their metaphysical constitution of the first order, based on a non-formal ontology.